2021
DOI: 10.3390/biology10121275
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Platelet Count in Patients with Severe Non-Plasmodium falciparum Malaria: A Systematic Review and Meta-Analysis

Abstract: The understanding of platelet biology under physiological and pathological conditions like malaria infection is critical importance in the context of the disease outcome or model systems used. The importance of severe thrombocytopenia (platelet count < 50,000 cells (µL) and profound thrombocytopenia (platelet count < 20,000 cells/µL) in malaria patients remains unclear. This study aimed to synthesize evidence regarding the risks of severe and profound thrombocytopenia in patients with severe non-Plasmodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
(254 reference statements)
1
0
0
Order By: Relevance
“…The present study found that depression of platelet count occurred in patients who had complicated malaria infection with symptoms as well as in persons with uncomplicated malaria without obvious symptoms. The afforementioned is in tandem with several other studies in other environs(Maina et al, 2010;Jojera et al, 2013;Gupta et al, 2019;Mahittikorn et al, 2021). In general, several reports have enunciated disseminated intravascular coagulopathy (DIC) as the most probable initiator of thrombocytopenia in acute malaria infections(Gérardin et al, 2002;Arif et al, 2016).…”
supporting
confidence: 52%
“…The present study found that depression of platelet count occurred in patients who had complicated malaria infection with symptoms as well as in persons with uncomplicated malaria without obvious symptoms. The afforementioned is in tandem with several other studies in other environs(Maina et al, 2010;Jojera et al, 2013;Gupta et al, 2019;Mahittikorn et al, 2021). In general, several reports have enunciated disseminated intravascular coagulopathy (DIC) as the most probable initiator of thrombocytopenia in acute malaria infections(Gérardin et al, 2002;Arif et al, 2016).…”
supporting
confidence: 52%